ANALISIS PENDAPATAN RUMAH TANGGA PETANI CENGKEH DI DESA TULAP KECAMATAN KOMBI KABUPATEN MINAHASA - Meidita Christine Kerap; Caroline B. D. Pakasi; Mex L. Sondakh (AGRI-SOSIOEKONOMI, 2018)
This study aims to identify the source of household income of clove farmers in Tulap Village, Kombi Sub-district, of Minahasa Regency. This study was conducted from February to March 2018. The data collection method used were primary data and secondary data. Primary data was obtained directly from the source through a survey by using questionnaires as the main instrument to collect data to clove farmers who also plant other crops such as peanuts, corn, and caberawit. The secondary data includ data published by the Central Bureau of Statistics as well as various literature related to the research topic. The results showed that the source of income of clove farmer household in Tulap Village, Kombi Sub-district, consisted of clove farming, other farming business, and those outside of farming business. The income pources outside farming were divided into farmers' and household members of farmers income. The highest income of clove farmers was obtained by the farmers' households, which meet the four sources of income, namely from clove farming, other farming, non-farm income and family members income with an average of Rp. 113,476,641 per year with a percentage of 15.22%. This proves if clove farmers have other farming businesses, have jobs outside the farm business, and household members have jobs and contribute to household income, the household will be more prosperous.*Ghmk*.